Diverse approaches to fighting infection in Northern Ireland - Damani, Nizam; Reid, Trudy; Keyes, Jemima (International Journal of Infection Control, 2008)
Sustained media coverage, staff shortages and a number of outbreaks were only few of the challenges facing the infection control team at Craigavon Area Hospital in 2005. However, better communication along with the introduction of initiatives such as Bug Watch, the Wipe it Out campaign and a link worker training programme, assisted in the successful reduction of Clostridium difficile infection rates. Multi-modal intervention initiated by the infection control led to the reduction in the Methicillin resistant Staphylococcus aureus (MRSA) bacteraemia rate. The hospital also achieved savings of £42,000 after reducing the inappropriate use of piperacillin/tazobactam.